The use of silicon-based tethers for the Pauson-Khand reaction - Dobbs, Adrian P.; Miller, Ian J.; Martinović, Saša (Beilstein Journal of Organic Chemistry, 2007)
A range of silicon-based tethers and promoters have been investigated for use in the development of a silyl-tethered Pauson-Khand reaction.

(untitled) - Khand, I. U.; Knox, G. R.; Pauson, P. L.; Watts, W. E.; Foreman, M. I. (J. Chem. Soc., Perkin Trans. 1, 1973)

(untitled) - Khand, I. U.; Knox, G. R.; Pauson, P. L.; Watts, W. E. (J. Chem. Soc., Perkin Trans. 1, 1973)

(untitled) - Bols, M.; Skrydstrup, T. (Chem. Rev., 1995)

(untitled) - Sieburth, S. M.; Fensterbank, L. (J. Org. Chem., 1992)

(untitled) - Stork, G.; Chan, T. Y.; Breault, G. A. (J. Am. Chem. Soc., 1992)

(untitled) - Nishiyama, H.; Kitajima, T.; Matsumoto, M.; Itoh, K. (J. Org. Chem., 1984)

(untitled) - Kagoshima, H.; Hayashi, M.; Hashimoto, Y.; Saigo, K. (Organometallics, 1996)

(untitled) - Reichwein, J. F.; Iacono, S. T.; Pagenkopf, B. L. (Tetrahedron, 2002)

(untitled) - Reichwein, J. F.; Iacono, S. T.; Patel, M. C.; Pagenkopf, B. L. (Tetrahedron Lett., 2002)

Abstracts of Papers - Brummond, K. M.; Sill, P. C. (224th National Meeting of the American Chemical Society, Boston, MA, 18.8.2002-22.8.2002, 2002)

(untitled) - Brummond, K. M.; Sill, P. C.; Rickards, B.; Geib, S. J. (Tetrahedron Lett., 2002)

(untitled) - Ishaq, S.; Porter, M. J. (Synth. Commun., 2006)

(untitled) - Dobbs, A. P.; Guesne, S. J. J.; Martinovic, S.; Coles, S. J.; Hursthouse, M. B. (J. Org. Chem., 2003)

(untitled) - Dobbs, A. P.; Venturelli, A.; Butler, L. A.; Parker, R. J. (Synlett, 2005)

(untitled) - Dobbs, A. P.; Martinovic, S. A. (Tetrahedron Lett., 2002)

(untitled) - Sugihara, T.; Yamada, M.; Ban, H.; Yamaguchi, M.; Kaneko, C. (Angew. Chem., 1997)
Angew. Chem., Int. Ed. Engl. 1997, 36, 2801–2804. doi:10.1002/anie.199728011

(untitled) - Sugihara, T.; Yamada, M.; Yamaguchi, M.; Nishizawa, M. (Synlett, 1999)

(untitled) - Perez-Serrano, L.; Casarrubios, L.; Dominguez, G.; Perez-Castells, J. (Org. Lett., 1999)

(untitled) - Park, K. H.; Son, S. U.; Chung, Y. K. (Org. Lett., 2002)

(untitled) - Iqbal, M.; Vyse, N.; Dauvergne, J.; Evans, P. (Tetrahedron Lett., 2002)

(untitled) - Jeong, N.; Lee, S. J.; Lee, B. Y.; Chung, Y. K. (Tetrahedron Lett., 1993)

(untitled) - Hoye, T. R.; Suriano, J. A. (J. Am. Chem. Soc., 1993)

(untitled) - Morimoto, T.; Fuji, K.; Tsutsumi, K.; Kakiuchi, K. (J. Am. Chem. Soc., 2002)

(untitled) - Shibata, T.; Toshida, N.; Takagi, K. (J. Org. Chem., 2002)

(untitled) - Denmark, S. E.; Cottell, J. J. (J. Org. Chem., 2001)

(untitled) - Brummond, K. M.; Chen, H. F.; Fisher, K. D.; Kerekes, A. D.; Rickards, B.; Sill, P. C.; Geib, S. J. (Org. Lett., 2002)

(untitled) - Kunai, A.; Ohshita, J. (J. Organomet. Chem., 2003)

(untitled) - Clive, D. L. J.; Kellner, D. (Tetrahedron Lett., 1991)

(untitled) - Maifeld, S. V.; Miller, R. L.; Lee, D. (Tetrahedron Lett., 2002)

(untitled) - Tanabe, Y.; Okumura, H.; Maeda, A.; Murakami, M. (Tetrahedron Lett., 1994)

(untitled) - Tanabe, Y.; Murakami, M.; Kitaichi, K.; Yoshida, Y. (Tetrahedron Lett., 1994)

(untitled) - Evans, P. A.; Cui, B.; Buffone, G. P. (Angew. Chem., Int. Ed., 2003)

(untitled) - Swisher, J. V.; Chen, H. H. (J. Organomet. Chem., 1974)

(untitled) - Swisher, J. V.; Chen, H. H. (J. Organomet. Chem., 1974)